Impact of Kasai portoenterostomy on liver transplantation outcomes: A retrospective cohort study of 347 children with biliary atresia. Issue 7 (July 2015) - Neto, Joao Seda; Feier, Flávia H.; Bierrenbach, Ana Luiza; Toscano, Cristiana M.; Fonseca, Eduardo A.; Pugliese, Renata; Candido, Helry L.; Benavides, Marcel R.; Porta, Gilda; Chapchap, Paulo
<x xml:space="preserve">Abstract</x> Biliary atresia (BA) is the main diagnosis leading to liver transplantation (LT) in children. When diagnosed early in life, a Kasai portoenterostomy (Kasai‐PE) can prevent or postpone LT. Instances of previous operations can result in difficulties during the LT. We hypothesized that a previous Kasai‐PE could affect LT outcomes. A retrospective cohort study of 347 BA patients submitted to LT between 1995 and 2013 at Hospital Sírio‐Libanês and A. C. Camargo Cancer Center was conducted. Patients were divided into those with a previous Kasai portoenterostomy early failure (K‐EF), Kasai portoenterostomy late failure (K‐LF), and those with no Kasai portoenterostomy (No‐K). Primary outcomes were patient and graft survival. A total of 94 (27.1%) patients had a K‐EF, 115 (33.1%) had a K‐LF, and 138 (39.8%) had No‐K before LT. Children in the K‐LF group were older and had lower Pediatric End‐Stage Liver Disease (PELD) scores. Patients in both K‐EF and K‐LF groups had more post‐LT biliary complications. After Cox‐multivariate analysis adjusting for confounding factors to determine the influence of Kasai‐PE on patient and graft survival, the K‐LF group had an 84% less probability of dying and a 55% less chance to undergo retransplantation. The K‐LF group had a protective effect on posttransplant patient and graft survival. When properly performed, the Kasai procedure can postpone LT and positively affect outcomes. Having a K‐EF and having not performed a Kasai‐PE had the same effect in patient and graft survival; however, a previous Kasai‐PE can increase post‐LT complications as biliary complications and bowel perforations. Liver Transpl 21:922‐927, 2015. © 2015 AASLD.